The Risk of Exposure to Cigarette Smoke in Anemia During Pregnancy - Riska Nur Safitri; Fariani Syahrul (Universitas Airlangga, 2015)
Anemia is defined as the state of hemoglobin (Hb) levels in the blood lower than normal values for groups of people according to age and sex. The prevalence of anemia in pregnant women according to Indonesia basic health research in 2007, 2010, and 2013 tends to increase. One risk factor for anemia is exposure to cigarette smoke. The purpose of this study was to study the comparison of the risk of cigarette smoke exposure to the incidence of anemia in pregnant women. This study uses a case-control design with a case: control ratio of 1: 2. The case sample was anemic pregnant women who examined their pregnancy at the Public health center (PHC) of Mojo Surabaya in 2015 and the control sample was anemic pregnant women. Case and control sampling using a simple random sampling method. Data analysis was performed by calculating the OR value at 95% CI using StatCalc on Epi Info. Independent variables are age, education level, employment status, family income, gestational age, birth spacing, multiple pregnancy history, parity, history of Antenatal Care (ANC), Mid-Upper Arm Circumference (MUAC), regular iron tablet (Fe) consumption. The results showed the risk of cigarette smoke exposure to the incidence of anemia in pregnant women OR = 4.09 (1.07 <OR <16.26), starting in the first trimester OR = 5.43 (1.12 <OR <34.41), number of active smokers 1-2 people OR = 5.54 (1.20 <OR <34.28), duration of exposure ≤ 15 minutes / day OR = 6.33 (1.28 <OR <40.53). The conclusion of this study is that exposure to cigarette smoke increases the risk of anemia in pregnant women. Pregnant women are advised to avoid cigarette smoke during pregnancy.